ANALISIS HUBUNGAN KEBIJAKAN MONETER DENGAN INFLASI DI INDONESIA - Nova Nova (Ekonomika : Jurnal Ekonomi dan Pembangunan, 2022)
This research aims to examine the relationship between monetary policy and inflation in Indonesia. The research method uses quantitative descriptive. The analysis model used is a vector autoregressive model. The research results show that the money supply has no long-term effect on inflation in Indonesia. The exchange rate has a long-term effect on inflation in Indonesia. Interest rates have no long-term effect on inflation in Indonesia.